GARAP GENDERAN DALAM GENDING LAMPAH TIGA - Wahyu Thoyyib Pambayun; Nanang Bayu Aji (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2020)
Gending lampah tiga composed by Harjasubrata in the 1950s. At the very beginning of its existence, lampah tiga composition focused and working on vocals, so gending lampah tiga has not been equipped with settled garap instruments. Most pengrawits find it hard to present gending lampah tiga, especially on ricikan gender, this is because the information about genderan lampah tiga is still limited. This article is entitled “Garap Genderan in Gending Lampah Tiga”, the problem  described in this article is how to present garap genderan in gending lampah tiga. The method that used to solve the problem in this article is to analyze and transcribe the presentation of gending lampah tiga, then interpreted.The writer hopes to provide an offer about how to interpret genderan in gending lampah tiga and to give a “little” contribution of thoughts for the development of karawitan science.